KRISIS EKONOMI DAN STRATEGI KELUARGA DALAM MEMPERTAHANKAN KEBUTUHAN NAFKAH - Ansari (Institut Agama Islam Ngawi, 2025)
Economic crises often have a significant impact on the family's ability to meet their livelihood needs, so the theme of this study is important to understand the strategies carried out by families in facing these challenges. This study aims to identify various family adaptive strategies during economic crises as well as analyze the factors that affect the success of these strategies. This study uses a qualitative method with a descriptive qualitative approach that is theoretical and based on literature review. The data source used is secondary data. The data collection technique is carried out through document study, namely tracing and analyzing library materials relevant to the focus of the research. The data analysis technique uses content analysis . The results of the study show that the strategies that are widely applied include income diversification, strict financial management, and the use of social networks, such as support from the community and relatives. Influential factors include family solidarity, member skills, access to resources, and government policy interventions. This research provides important insights into the role of family and community collaboration in improving economic resilience during a crisis. Keywords: Economic crisis, family strategy, maintenance.